Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The Ideological and Strategic Dimensions of American Support for Israel During the Gaza WarMr. Akram Mohammad Ali Chamas2. Methods for enhancing AI applications in improving schedule and resource management in agile infrastructure projects in KSADr. Anwar Mohammed Gismallah Mohammed3. The Guarantees of the Public Employee in the Administrative Investigation (A Comparative Study between the Saudi System and the Egyptian Law)Ms. Dareen Yousef Al-Thaqafi4. The Impact of the University Education (Research) index on the Global Competitiveness of the United Arab Emirates During the Period (2021-2022)Dr. Shawk Hasan Mahdi5. The Impact of Digital Transformation on Governance Principles at the Royal Oman Police  from the Perspective of External StakeholdersDr. Azza Said Hilal Al-Sharji, Dr. Khalifa Mohammed Said Al-Fathi6. Human resource management (HRM) practices and employee job satisfaction: The case of a public corporation in QatarMs. Baina Hamad Al-Marri7. Assessing the impact of AI influencers on customer engagement for non-luxury brands in EgyptMs. Nesma Ibrahim Amir Abdelrazek, Ms. Alaa Tarek Khalil
Keywords: Journal of Economic, Administrative and Legal Sciences